The Impact of Additive Noise on Polarimetric RADARSAT-2 Data Covering Oil Slicks - Espeseth, Martine; Skrunes, Stine; Brekke, Camilla; Johansson, Malin (IGARSS 2019 - 2019 IEEE International Geoscience and Remote Sensing Symposium, 2019)
Source at https://doi.org/10.1109/IGARSS.2019.8899787 . We attempt to understand how a set of well known polari-metric Synthetic Aperture Radar (SAR) features are impacted by the additive system noise for mineral oil and produced water slicks. For this, we use quad-polarimetric SAR scenes from Radarsat-2. Oil slicks at sea can be detected using SAR instruments, and the dual- (HH-VV) and quad-polarimetric modes can provide additional information about the characteristics of the oil. Therefore the increase in polarization dimensionality may be beneficial in a potential clean-up situation. For example, characterization could aid in separating different types of oil slicks, like mineral oil and produced water as studied here. Oil slick characterization using scattering properties can only be performed if the returned signal is well above the noise floor. To avoid misinterpretation it is important to understand how the noise impacts the measured radar signal. Most of the features investigated in this study were to a larger degree influenced by the additive noise. Further, a backscatter signal level of 10 dB above the noise floor is identified as necessary to support analysis of the scattering properties within the oil slicks without too much noise contamination of the signal. The mineral oils and produced water slicks showed similar polarimetric behavior, despite their chemical and physical differences at release.